Ideology, psychology, and law - Hanson, Jon.; Jost, John T. (Oxford : Oxford University Press, 2012)
Over the last decade or so, political scientists and legal academics have begun studying the links between ideologies, on one hand, and legal principles and policy outcomes on the other. This book brings together international experts on those topics to examine the sometimes unsettling interactions between psychology, ideology, and law.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Apr. 18, 2012).
Keywords: Interpersonal relations; Social psychology; Ideology; Psychology; Law